2012
DOI: 10.1590/s1516-35982012000200028
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of Santa Inês sheep raised in confinement with diet containing cactus pear replacing corn

Abstract: -The objective of this study was to assess the tissue component yields and the physical, chemical and sensory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
5
9
2
1
Order By: Relevance
“…Costa et al (2012) analyzed the chemical composition of Santa Inês sheep meat and found values close to the results of the present study: 75.6% humidity, 2.5% ethereal extract, 20.7% protein, and 1.02% ashes. Hood and Thornton (1979) found that there is an increase in the number of fat cells in sheep Santa Ines in the growth phase between 28 and 45 kg body weight.…”
Section: Resultssupporting
confidence: 89%
“…Costa et al (2012) analyzed the chemical composition of Santa Inês sheep meat and found values close to the results of the present study: 75.6% humidity, 2.5% ethereal extract, 20.7% protein, and 1.02% ashes. Hood and Thornton (1979) found that there is an increase in the number of fat cells in sheep Santa Ines in the growth phase between 28 and 45 kg body weight.…”
Section: Resultssupporting
confidence: 89%
“…The L * value obtained in the current study (37.6 as average) indicated an acceptable colour for consumers, since L * values equal to or greater than 34 are considered acceptable for lamb meat . However, the a * value obtained at the current study (15.0 as average) was lower than that found by Costa et al . (19.4 as average) using diets replacing maize by spineless cactus.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, the inclusion of spineless cactus in the finishing diets for sheep affected the FA profile, decreasing the saturated FA content and improving the monounsaturated and polyunsaturated FA amounts . However, data about the influence of including spineless cactus in the finishing diets of lambs on meat quality is scarce . Therefore, the aim of this work was to assess the impact of the inclusion of spineless cactus at four levels (0, 150, 300 and 450 g kg −1 of dry matter, DM) in replacement of Tifton hay in the finishing diet of lambs and to evaluate how it affects to the physicochemical properties and sensory characteristics of meat.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborando com a redução desta relação está o resultado linear decrescente verificado para o índice de musculosidade da perna (IMP), que é tanto maior quanto maior for a quantidade de carne nas carcaças (Moreno et al, 2010), sendo o inverso também verídico. Contudo, apesar da redução do IMP, o valor médio obtido neste estudo (0,36 g cm -1 ) é semelhante ao reportado por Costa et al (2012) para ovinos da mesma raça.…”
Section: Tabelaunclassified